Virtual Writing Tutor (VWT) on Students’ Writing Skill Improvement at Writing Class - Rafika Dewi Nasution; Marisi Debora; Bahagia Saragih; Johannes Jefria Gultom; Safrida Lubis (Asian TESOL Journal, 2023)
The study aimed to investigate Virtual Writing Tutor (VWT) on students’ writing skill at writing class. The study involved 30 participants taking writing subject at English and Literature Department, Language and Art Faculty, Universitas Negeri Medan. The qualitative method was conducted in this study. An observation sheet, questionnaire, and interview guidance were the instruments of study. The findings of the study showed that 100% of students are interested in using the media in practicing their writing skills. However, 45% of students stated that the choice of essay types was limited. Furthermore, 15% of students stated that there are features that cannot be accessed for free because they must have a premium (paid) account. Thus, , it is still necessary to be highlighted that using VWT is not the only way to get better at writing. It ought to be utilized in conjunction with classroom instruction and lecturer directions.